Professional Atitude Can Cause to Perch Plagiarism - Martaadisoebrata, Djamhoer (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
A calling requiring specialize knowledge and often long and intensive preparation including instruction and skills and methods as well as in the scientific, historical and scholarly principles, underlying such skills and methods, maintaining by force or organization or concern opinion, high standard of achievement and conduct, and committing its members to continue study and to a kind of work which has for prime propose the rendering of public service.